Pengaruh Efek Kontaminasi Isolator KeramikTerhadap Rugi DayaSaluran Udara Tegangan Tinggi - Ruwah Joto; Dhesah Kharisma, Dhimas; Tresna Umar Syamsuri; Aly Imron (Politeknik Negeri Malang, 2023)
In meeting consumers' needs for electric power continuously, the reliability of electric power distribution is something that needs to be considered. One of the reliability parameters is the network's ability to distribute power from generators continuously, with the allowable voltage and frequency quality. For this reason, the presence of an insulator in the power distribution system is very important considering its function is to separate live conductors from their supports. If the isolation properties do not function, a voltage failure will occur so that power distribution will stop, resulting in low system reliability. From the data from the calculation results of 150 kV high voltage overhead line power losses due to flashovers on insulators installed in each fouling area, it is clear that increasing the contaminant value will make it easier for flashovers to occur which cause very large power losses and conversely, insulators that are clean make it difficult. the occurrence of flashover so as to reduce power losses on the transmission line. The appropriate insulator to use is the fog type, because the diameter is wider, increasing the propagation distance so that the insulator's ability to withstand greater voltage